The role of mental health to overcoming the coronavirus disease-19 pandemic - Dania, Ira Aini; Novziransyah, Nanda (Faculty of Medicine, Universitas Trisakti, 2021)
The current coronavirus disease-19 (COVID-19) pandemic has changed the order of social life; the efforts made to tackle this pandemic have sometimes raised various obstacles related to norms, ethics and culture. An increased risk of COVID-19-associated mental disorders is found in many communities, causing excessive emotional reactions such as feelings of pressure, leading to unhealthy behavior. This situation confirms that health care providers have a key role in dealing with emotional disturbances that occur as a form of pandemic response. Public health emergencies can affect the health, safety and well-being of every individual as well as the social stigma in connection with the COVID-19 pandemic. Various mental health studies related to disasters have determined that emotional distress is widespread and can also be found in populations related to COVID-19. There are various kinds of risk factors that have an impact on health workers during the COVID-19 pandemic, including social isolation, lack of support, and concerns about safety of family members. We included published, observational and experimental studies that reported the mental health effects on health workers during the COVID-19 pandemic. Efforts made by policy holders, especially in the health sector, have greatly contributed to the response to the pandemic, but not all of them can run smoothly, several steps and policies in the health sector must involve many stakeholders in order to realize the expected efforts. The main purpose of this review paper was to not only focus on health workers, but include the communities in overcoming the COVID-19 pandemic.